Trends in the use of high technology solutions for cybersecurity of critical infrastructure - Ivanova, Yoana (Yearbook Telecommunications, 2019)
The aim of the paper is to present innovative technologies that contribute to strengthening cybersecurity of critical infrastructure. It focuses on trends in the use of high-tech solutions for cybersecurity of critical infrastructure. They are analyzed the capabilities of the next-generation cybersecurity model, as well as the role of the simulation modelling and expert systems in the process of identifying and preventing cyber attacks. The main result of the study is the description of the overall sequence of steps to be completed in a model in order to a simulation study of the impact of a DoS â€“ attack to it. The applied conributions are expressed in developing the algorithms in the form of block diagrams because of the comparative clarity and accessibility of this approach. Therefore, they are suitable for implementation in professional simulation environments. Ð¢he types of algorithms and their properties, as well as the symbolism of the geometric blocks used are explained in detail and supported by examples of author’s empirical studies conducted in the selected simulation products